Effects of commercial fatty acids, organic acids and mineral supplementation on milk yield and blood characteristics of dairy goats in selected farms in Kelantan, Malaysia. (Journal of Tropical Resources and Sustainable Science (JTRSS), 2019)
Milk production of dairy goats raised by smallholders in Malaysia are usually very low with which are mainly attributed to poor nutrition. This study was aimed at evaluating the benefits of supplementing commercial fatty acids, organic acids and chelated minerals for enhancing milk production. Eighty Saanen dairy goats in the stage of mid-lactation were selected from 8 smallholder farms in Kelantan, Malaysia to evaluate their blood profile and mineral status in relation to their daily rations. Based on estimated dry matter intake (DMI), 50% of the animals were found not adequately fed, with deficit of 6% - 12% from the targeted DMI. Initial screening of the blood revealed that red blood cell (RBC), haemoglobin (HGB), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) values were marginally low while sodium (Na) was deficient. Based on these findings, 6 groups of 10 Saanen dairy goats from 6 farms were selected from the above 8 farms for the second trial. Five animals in each group were supplemented with either commercial fatty acids, organic acids and chelated minerals, while another 5 were not supplemented and fed only on routine rations. A formulated feed mixture, which comprised of PKC, NaCl, CaCO3, zeolite and mineral-vitamin premix at the rate of 100, 15, 15, 5 and10 g/day respectively were provided to the supplemented groups on top of routine rations. Supplementation of fatty acids (Extima 100, Extima 300, Extima Star and Extima 100 + Extima Star at the rate of 100, 100, 100 and 50+50 g/day), chelated mineral (POWERMIN 4COW/CATTLE+P, 400g/day) and organic acid (ORGACID, 100 g/day) to the respective supplemented groups resulted in improvement in certain blood characteristics and enhanced Na level. The improvement in milk yield associated with supplementation was between 12 – 16%. However, body condition score (BCS) of the supplemented groups were improved as compared to those non-supplemented. The findings revealed that supplementation of the above supplements, even with limited amount of a formulated feed mixture were less effective in enhancing milk yield of the dairy goats raised under the smallholders feeding condition.
Keywords: Blood parameters; Chelated minerals; Fatty acids; Organic acid; Saanen